ANALISIS YURIDIS ATAS TINDAK PIDANA OLEH PEDOFILIA TERHADAP ANAK DI BAWAH UMUR UNTUK MEWUJUDKAN PERLINDUNGAN KONSTITUSIONAL ANAK - Rinaldo Saleleubaja; Laily Washliati; Juhrin Pasaribu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Juridical analysis of criminal acts by pedophiles against minors to realize the constitutional protection of children there is a formulation of the problem which includes legal arrangements regarding criminal acts by pedophiles against minors to realize the constitutional protection of children and secondly concerning the implementation, obstacle factors and solutions to criminal acts by pedophiles against minors to realize the constitutional protection of children. The type of research used is normative and supported by empirical research as well as data collection techniques conducted through interviews with parties related to the research topic. In addition, the author also conducts library research through books and literature related to the research topic. Furthermore, the data obtained were analyzed qualitatively which was then presented descriptively. Based on the results of research and discussion in the implementation of criminal acts by pedophiles against minors to realize the constitutional protection of children, the results of this study are in the form of laws and regulations that are used to protect victims of pedophilia crimes based on the Criminal Code and Law Number 35 of 2014 concerning amendments to Law Number. 23 of 2002 concerning child protection. The problems discussed in this thesis are the process of criminal acts by pedophiles against minors to realize the constitutional protection of children as well as discussing the obstacles and solutions faced by investigators in committing pedophilic crimes against minors. This research shows that the main actors are adults and also the closest people. The obstacle in the criminal act of pedophilia is the lack of information from the victim, as for the solutions to overcome the problem of special attention from parents, the community, and law enforcement. Keywords: Law Enforcement, Crime, Pedophilia